Worst-case equilibria in first-price auctions - Vitali Gretschko; Helene Mass (Theoretical Economics, 2024)
The usual analysis of bidding in first-price auctions assumes that bidders know the distribution of valuations. We analyze first-price auctions in which bidders do not know the precise distribution of their competitors' valuations, but only the mean of the distribution. We propose a novel equilibrium solution concept based on worst-case reasoning. We find an essentially unique and efficient worst-case equilibrium of the first-price auction, which has appealing properties from both the bidders' and the seller's point of view.
Keywords: D44; D81; D82; 330; Auctions; uncertainty; worst-case equilibria